Effectiveness of Bangun-Bangun Leaf (Coleus Amboinicus Lour) on Breast Milk Production in Post Partum Mothers - Mendawaty Pandiangan; Lili Farlikhatun (Global Health Science Group, 2023)
The target of achieving exclusive breastfeeding is still difficult to achieve optimally due to several things including disruption or non-smooth milk expenditure. Data in Indonesia shows exclusive breastfeeding coverage is only 42%. Various efforts were made, one of which was by exploring the potential of bangun-bangun leaf herbs to increase breast milk production. The purpose of this study was to measure the effectiveness of the bangun-bangun leaf intervention on breast milk production. This research was quasy experimental design. The location used for this research is in the PMB Mendawaty working area in May - June 2023. The study sample was 32 post partum in which there were 16 control groups and 16 intervention groups giving bangun-bangun leaf extract. The bivariate analysis used is the Chi-Square test. The results of the chi-square analysis resulted in an odds ratio value (OR: 2.14; 95% Confident Interval 1.08 – 4.23; p value 0.033) it can be concluded that giving bangun-bangun leaf extract can increase breast milk production up to 2 times compared to not consuming bangun-bangun leaves and is statistically significant.